Graduation modalities and the development of manaGement skills in industrial enGineerinG students from the universidad distrital - Nova Arevalo, Néstor Armando; Pinzón, Wilson A.; Torres M, Orlando (Ingeniería Solidaria, 2012)
The authors present the results of the research project “Graduation modalities and the development of management skills in industrial engineering students from the Universidad Distrital”, carried out in the Universidad Distrital Francisco José de Caldas in 2011. This research was aimed to analyze the effects of graduation modalities in the skills of students and graduates of the industrial engineering program of this university. The authors make a statistical comparison of the skills in three graduation modalities: internship, research, and thesis, with the ones of an interdisciplinary group of engineers. Moreover, they use the variance analysis of the results obtained in two different sessions of assessment center. The first session was carried out at the beginning of the graduation process of the students, the second one at the end of it. The study showed some significant differences in inter and intrapersonal, emotional, and technical skills; variations in the management skills of the test subjects were also observed.